Relationship between diet and seborrheic dermatitis - Funda Tamer (Our Dermatology Online, 2018)
Background: Seborrheic dermatitis is a chronic inflammatory skin disease that affects 1-10% of the general population. Malassezia yeasts, immune response and emotional stress have been implicated in the etiology of seborrheic dermatitis. However, the effect of diet on development of seborrheic dermatitis is still controversial. This study investigates the differences in the frequency of consumption of foods and food groups between patients with seborrheic dermatitis and healthy individuals. Material and Methods: Fifty-one patients with seborrheic dermatitis of the scalp (28 female, 23 male) and 50 healthy individuals within the control group (30 female, 20 male) have been included in this study. The mean age of the patients and control group were 30.6±11.4 years and 32.7±10.7 years, respectively (p=0.35). Dietary habits were evaluated by a questionnaire which includes frequency of intake of meat, processed meat, chicken, fish, egg, legume, milk, dairy products, fruit, vegetable, bread, tea, coffee, coke, fast food, sugar, pasta, rice, chocolate, cake, cookie and pie. The questionnaire included options like every day, 3-5 times a week, 1-2 times a week, twice a month, once a month and none. Results: The frequency of intake of foods in the questionnaire was simlar between patients and healthy individuals except for vegetables. Vegetable consumption was significantly more common among patients than healthy individuals (p=0.04). Conclusions: The results showed that dietary habits were not associated with increased risk of seborrheic dermatitis.